The automotive sector in EU-CEECs: Challenges and opportunities - Doris Hanzl-Weiss (FIW - Research Centre International Economics, 2022)
The global automotive sector is undergoing major structural changes which in the next decades will pose significant challenges to the sector, but also offer opportunities. Highlighting three major disruptive trends, (i) shifts of global automotive production towards Asia, in particular China, (ii) trends in e-mobility, and (iii) problems in supply chains, this article shows how Austria and the Central and East European automotive sector have faced these shifts. Overall, the EU-CEE countries have benefited from the relocation of automotive companies to emerging countries and have been integrated into global, in particular German supply chains during the last thirty years. The e-revolution started off in 2020 and the EU-CEE had a rather good start. As the automotive industry is a key sector in the region, the electric transformation is vital for their future. While there are some positive trends, risks are manifold, and further efforts have to be undertaken so as not to be left behind.
Keywords: 330